Daring young men : the heroism and triumph of the Berlin Airlift, June 1948 - May 1949 - Reeves, Richard 1936-2020 (Simon & Schuster Paperbacks, 2011)
The author of the bestsellers "President Nixon" and "President Kennedy" details the harrowing journey of two men who risked their lives to defy the Soviet blockade intended to drive Western powers out of Berlin.